(DE)FORMATION JOURNEY IN THE ELIAS CANETTI AUTOBIOGRAPHY NARRATIVE - Matos-de-Souza, Rodrigo (Revista de Estudos em Educação e Diversidade - REED, 2021)
This article addresses the Elias Canetti’s autobiography from a formative point of view searching for another meaning for the trip concept, in which desire and pleasure are not present, as one would expect from a sightseeing tour or trekking, but a journey that, involuntary and forcibly, crosses the individual, (de)forming them. Accordingly, the refuge, the escape, the self-exile, they relate a path of personal tragedies that gains other meanings when narrated. Elias Canetti’s autobiographical narrative is divided in three volumes – “The tongue set free”, “The torch in my ear” and “The play of the eyes” – and tells us about the author’s migratory routes across a Europe crumbling under wars and totalitarian regimes which arose in the first half of the 20th century. His testimony is an account of a world that catches a glimpse of totalitarian experiences and the trivialization of evil that marks the history of Western civilization. Elias Canetti’s writings narrates the roads he had to take to avoid direct contact with the Great Wars, and exposes certain (de)formative aspects of migration, as well as how these experiences, so open to uncertainties and rid of any guaranties, appear before the eyes of a young man from a rich family, whose mother tried to protect from the perils of the world. This feature is one of many highlights, a sine qua non element in his stories, because that is where all the terror and pain lie for those who flee their homeland to venture into foreign lands in an almost instinctive attempt to survive. It is in this sense that we work the concept of (de)formation in its relation with the concept of journey.